Produção de metano a partir de vinhaça e melaço em reatores UASB termofílicos, em dois estágios - Santana Junior, Aureo Evangelista [UNESP] (2013)
An adaptation of mesophilic inoculum for thermophilic anaerobic conversion of vinasse sugarcane, in two UASB reactors installed in series R1 and R2 was initially assessed. In the sugarcane off-season we evaluate the use of sugarcane molasses and again vinasse to produce methane. The reactors were maintained at the controlled temperature of 55 ° C and operated for 387 days. The organic loading rate (OLR) applied in R1 were increased from 0.15 to 12.50 g CODtotal (L d)-1 .The best removal efficiencies of CODtotal and CODdiss were observed with and applying (OLRs) from 0.15 to 3.50 and 3.50 7.0 g CODtotal (L d)-1, using a vinasse as influent and were 55 and 51%, respectively, for the system (R1 + R2). The higher values of volumetric methane production, were 0.205 and 0.350 L CH4 (L d)-1 and occurred with application of (OLRs) from 7.5 to 12.5 and 6.5 to 11.3 g CODtotal (L d)-1 using vinasse as influent on R1 and R2, respectively. The results demonstrated the possibility of thermophilic anaerobic treatment of vinasse in UASB reactors, with good removal of COD and after start up, increased volumetric methane production and methane percentage present in this biogas. Fertilizer quality of this effluent was obtained due of low concentration reduction of nutrients, were 37 and 70% removal efficiencies for Kjeldahl nitrogen (NK) and total phosphorus, respectively, possibly because N and P supplementation